Effects of acute exercise on visual reaction time - Ando, S.; Kokubu, M.; Kimura, T.; Moritani, T.; Araki, M. (International Journal of Sports Medicine, 2008)
We examined the effects of acute exercise on reaction time to visual stimuli presented in the central portion and periphery of the visual field. Twelve participants performed reaction time tasks at rest and during cycling at 65 % peak oxygen uptake in two visual conditions. We used circular black-and-white checkerboard patterns as visual stimuli. The participants were asked to respond as quickly as possible to pattern reversal of the visual stimulus by releasing a response button. Reaction time was fractionated into Premotor time and Motor time. Premotor time in the peripheral condition significantly increased (p < 0.025) during exercise (mean ± SE; 195.9 ± 7.9 ms) from that at rest (183.7 ± 6.8 ms). Premotor time in the central condition did not differ between at rest (185.3 ± 7.6 ms) and during exercise (188.4 ± 6.6 ms). These data suggest that the ability to respond to visual stimuli presented in the periphery of the visual field is vulnerable to moderate to severe exercise, as compared with the ability to respond to visual stimuli presented in the central portion of the visual field. An exercise-induced increase in arousal level and a consequent narrowing of attentional focus would explain the present results.